Are there multiple circadian clocks in plants? - Hotta, Carlos T (Landes Bioscience, 2008)
We have reported that Arabidopsis might have genetically distinct circadian oscillators in multiple cell-types.1 Rhythms of CHLOROPHYLL A/B BINDING PROTEIN2 (CAB2) promoter activity are 2.5 h longer in phytochromeB mutants in constant red light and in cryptocrome1 cry2 double mutant (hy4-1 fha-1) in constant blue light than the wild-type.2 However, we found that cytosolic free Ca(2+) ([Ca(2+)](cyt)) oscillations were undetectable in these mutants in the same light conditions.1 Furthermore, mutants of CIRCADIAN CLOCK ASSOCIATED1 (CCA1) have short period rhythms of leaf movement but have arrhythmic [Ca(2+)](cyt) oscillations. More important, the timing of cab1-1 (toc1-1) mutant has short period rhythms of CAB2 promoter activity (∼21 h) but, surprisingly, has a wild-type period for circadian [Ca(2+)](cyt) oscillations (∼24 h). In contrast, toc1-2, a TOC1 loss-of-function mutant, has a short period of both CAB2 and [Ca(2+)](cyt) rhythms (∼21 h). Here we discuss the difference between the phenotypes of toc1-1 and toc1-2 and how rhythms of CAB2 promoter activity and circadian [Ca(2+)](cyt) oscillations might be regulated differently.